BERBAGAI BERKAH BID’AH NYADRAN (INOVASI PEMBELAJARAN AGAMA)DALAM BUDAYA ISLAM JAWA - Daryono .; Dini Anggraheni (Universitas Aki, 2018)
This research aims at understanding bid’ah definition and its technical application, especiallythe ways to pray for the Lates that in Javanese Islamic culture is called nyadran with its variousblessings (merits) and moral values. The type of this research is library research. The source ofthe data includes hadits from Prophet Muhammad SAW and works from experts that explainmoral values of Javanese Islamic culture and nyadran with its various blessings. The method ofthis research is content analysis with sociological approach that has characteristic as sociologicinterpretation. The result of this research gives understanding about definition, types, andjurisdiction of bid’ah mainly when commemorating somebody’s death through delivering prayercalled as nyadran in Javanese Islamic culture. Through that understanding, it is expected tobecome the direction that is following the age.Keywords: blessings, Nyadran, Javanese Islamic culture.